THE PSYCHOLOGICAL ESSENCE OF THE CONCEPT OF HEALTHY THINKING (Universal International Scientific Journal, 2026)
This article sheds light on the psychological essence of the concept of healthy thinking. The psychological factors of healthy thinking are analyzed.
Keywords: rational, creative, logical